2012
DOI: 10.1111/j.1744-7410.2012.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and regeneration of midgut epithelial cells in Lithobius forficatus (Chilopoda, Lithobiidae)

Abstract: Lithobius forficatus (Myriapoda, Chilopoda, Lithobiidae) is a widespread species of centipede that is common across Europe. Its midgut epithelial cells are an important line of defense against toxic substances that originate in food, such as pathogens and metals. Despite this important role, the biology of the midgut epithelium is not well known. Here we describe the ultrastructure of the midgut epithelium, as well as the replacement of degenerated midgut epithelial cells. The midgut epithelium of L. forficatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 61 publications
(189 reference statements)
1
27
0
Order By: Relevance
“…Circadian rhythms in centipedes affect, for example, the ecological niches that they occupy or the homeostasis of the animals (Mead 1970;Amouriq 1967;Lewis 1981;Tuf et al 2006). During our previous studies, we described the proliferation of regenerative cells, which is dependent on (S. cingulata- Chajec et al 2014) or is independent of the day/night cycle (L. forficatus- Chajec et al 2012) as well as the process of autophagy, which proceeded in a continuous manner and did not depend on the day/night cycle (both S. cingulata and L. forficatus) (Rost-Roszkowska et al 2015a). While analyzing the structure and ultrastructure of the endodermal region of the digestive system of the abovementioned species of centipedes (Chajec et al 2012(Chajec et al , 2014, we also observed signs of apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms in centipedes affect, for example, the ecological niches that they occupy or the homeostasis of the animals (Mead 1970;Amouriq 1967;Lewis 1981;Tuf et al 2006). During our previous studies, we described the proliferation of regenerative cells, which is dependent on (S. cingulata- Chajec et al 2014) or is independent of the day/night cycle (L. forficatus- Chajec et al 2012) as well as the process of autophagy, which proceeded in a continuous manner and did not depend on the day/night cycle (both S. cingulata and L. forficatus) (Rost-Roszkowska et al 2015a). While analyzing the structure and ultrastructure of the endodermal region of the digestive system of the abovementioned species of centipedes (Chajec et al 2012(Chajec et al , 2014, we also observed signs of apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Still, it is probable that these cells may divide at specific periods of the life cycle (e.g. during moulting) as has been described or sug- Rost-Roszkowska et al, 2007;Hakim et al, 2010;Nardi et al, 2010;Chajec et al, 2012). Finally, several cells forming the layer of the new/young digestive cells have been observed between crescent-like cells and digestive cells.…”
Section: Discussionmentioning
confidence: 95%
“…Midgut progenitor cells that differentiate into all types of the midgut epithelial cells have been described mainly for arthropods. They are described as cells which show the features of both midgut stem cells and digestive cells (Martins et al, 2005;Cruz et al, 2011;Chajec et al, 2012). The amount of reserve material (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platyhelminths, Nemertea, Annelida, Mollusca (2), Chelicerata (5) and Crustacea (6, 7) perform both intra and extracellular digestion. Ctenophora, Onycophora, Tardigrada (2), Myriapoda (8,9), Hexapoda (10) and Vertebrata (4) digest the food primarily extracellularly.…”
Section: General Considerations About the Digestive Processmentioning
confidence: 99%